Pengaruh Pendistribusian Dana Zakat Terhadap Kesejahteraan Mustahik Melalui Program Pendidikan Yakesma Kota Sorong - Ika Nurhaliza Fatmalasari; Fardan Abdillah M (At-Thariqah: Jurnal Ekonomi, 2024)
Poverty is problematic, therefore zakat is present as an instrument for the economic development of the people that can eradicate poverty. With the problems that occur in Indonesia, namely the welfare gap, the government has formed an institution for distributing funds according to Islamic law in Indonesia, namely the Zakat Amil Institution and the Zakat Amil Agency. The existence of an education program to distribute zakat funds for welfare at the Sorong City Yakesma institution is expected to be able to provide a real contribution to the welfare of its mustahik, especially in the need for educational financing. The purpose of this study is to determine the effect of the zakat fund distribution variable (X) on the welfare of mustahik (X) through the Sorong City Yakesma education program (M). The research method is quantitative, data collection techniques are observation, questionnaires and documentation. Hypothesis testing uses the t-test and F-test using SPSS tools. The results of the study indicate that the variables of the Distribution of Zakat Funds on the welfare of mustahik and zakat funds on education programs have a positive and significant effect. The Education Program on the welfare of mustahik has a negative effect and partially has a significant effect. Meanwhile, the Distribution of Zakat Funds to the Welfare of Mustahik through the Education Program proves that the education program is not able to mediate the relationship between the influence of the distribution of zakat funds and the welfare of mustahik.